The importance of preoperative and perioperative Narrow Band Imaging endoscopy in the diagnosis of pre-tumor and tumor lesions of the larynx - Filipovsky, Tomas; Kalfert, David; Lukavcova, Eva; Zavazalova, Sarka; Hlozek, Jiri; Kovar, Daniel; Astl, Jaromir; Holy, Richard (Journal of applied biomedicine, 2023)
INTRODUCTION: Narrow band imaging (NBI) is an endoscopic imaging method intended for the diagnosis of mucosal lesions of the larynx that are not visible in white-light endoscopy, but are typical of pre-tumor and tumor lesions of the larynx. THE PURPOSE OF THE STUDY: To compare preoperative/perioperative white light endoscopy and NBI endoscopy with the results of histopathological examinations in pre-tumor and tumor lesions of the larynx. METHODS: A prospective study, over a period of five years (5/2018-5/2023), included 87 patients with laryngeal lesions aged 24-80 years. We evaluated preoperative/ perioperative white light and NBI endoscopy, established a working prehistological diagnosis, and compared this with the definitive histopathological results of laryngeal biopsies. RESULTS: In relation to the definitive histology score, a statistically significant correlation was found between the evaluation of the finding and the definitive histology for preoperative and perioperative white light endoscopy and NBI endoscopy (p < 0.001). Both methods showed higher precision when used perioperatively. CONCLUSION: NBI endoscopy is an optical method that allows us to improve the diagnosis of laryngeal lesions, perform a controlled perioperative biopsy, and refine the surgical scope. The NBI endoscopy is a suitable method for the diagnosis of early cancerous lesions of the larynx. The use of preoperative/perioperative NBI endoscopy allowed us to achieve a high level of agreement correlation (p < 0.001) between the prehistological working diagnosis and the final histopathological result. The NBI method proves its application in the diagnosis of pre-tumor and tumor lesions of the larynx.
Keywords: Laryngeal tumor; Histopathological results; nádory hrtanu; Perioperative endoscopy; Narrow Band Imaging; Laryngeal Neoplasms; Endoscopy, Gastrointestinal; Endoscopy; Prospective Studies; lidé; Larynx; gastrointestinální endoskopie; Preoperative endoscopy; úzkopásmové zobrazení; larynx; Humans; Narrow band imaging; prospektivní studie